Regulation of endothelial and epithelial barrier functions by peptide hormones of the adrenomedullin family - García-Ponce, Alexander (Tissue Barriers, 2016)
The correct regulation of tissue barriers is of utmost importance for health. Barrier dysfunction accompanies inflammatory disorders and, if not controlled properly, can contribute to the development of chronic diseases. Tissue barriers are formed by monolayers of epithelial cells that separate organs from their environment, and endothelial cells that cover the vasculature, thus separating the blood stream from underlying tissues. Cells within the monolayers are connected by intercellular junctions that are linked by adaptor molecules to the cytoskeleton, and the regulation of these interactions is critical for the maintenance of tissue barriers. Many endogenous and exogenous molecules are known to regulate barrier functions in both ways. Proinflammatory cytokines weaken the barrier, whereas anti-inflammatory mediators stabilize barriers. Adrenomedullin (ADM) and intermedin (IMD) are endogenous peptide hormones of the same family that are produced and secreted by many cell types during physiologic and pathologic conditions. They activate certain G-protein-coupled receptor complexes to regulate many cellular processes such as cytokine production, actin dynamics and junction stability. In this review, we summarize current knowledge about the barrier-stabilizing effects of ADM and IMD in health and disease.